2018
DOI: 10.1108/cg-01-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Are female leaders more efficient in family firms than in non-family firms?

Abstract: Purpose The aim of this study is to investigate whether female leaders are more efficient in family firms than in non-family firms. Design/methodology/approach This paper uses a unique database of ownership and leadership in private Swedish firms that makes it possible to analyze differences in firm performance due to female leadership in family and non-family firms. The analysis is based on survey data merged with micro-level data on Swedish firms. Only firms with five or more employees are included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 60 publications
2
46
1
Order By: Relevance
“…Joint venture size is lower for family businesses and the t-statistics indicate that the difference is significant at 1%. Consistently with literature (Cheung et al, 2005;Chen et al, 2005;Lam and Lee, 2008;Bjuggren et al, 2018), CEO Family control and influence on JV investment duality and the percentage of women on the board, as well as human capital efficiency, are significantly different at the 1% significance level between the two samples while there is evidence of difference at the 5% level for the proportion of link-type joint ventures.…”
Section: Resultssupporting
confidence: 87%
“…Joint venture size is lower for family businesses and the t-statistics indicate that the difference is significant at 1%. Consistently with literature (Cheung et al, 2005;Chen et al, 2005;Lam and Lee, 2008;Bjuggren et al, 2018), CEO Family control and influence on JV investment duality and the percentage of women on the board, as well as human capital efficiency, are significantly different at the 1% significance level between the two samples while there is evidence of difference at the 5% level for the proportion of link-type joint ventures.…”
Section: Resultssupporting
confidence: 87%
“…This kind of family agenda is in line with SEW protection. However, this may weaken the internal governance system and yield lower performance (Bjuggren, Nordström and Palmberg, 2018). Second, daughters may be less prepared for succession (Nelson and Constantinidis, 2017).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Despite these facts, the study of female leadership and its impact in firm performance of family firms has not received much attention. The study of Bjuggren [41] is an exception where differences in firm performance due to female leadership in family and non-family firms was analyzed and the results indicated that female leadership makes much more of a positive difference on performance in family firms while this effect is negative in non-family firms.…”
Section: Hypothesis 1 Female Executives Exert a Positive Effect On Fmentioning
confidence: 99%